PENGARUH LAYANAN INFORMASI TERHADAP PENGENDALIAN DIRI SISWA KELAS X IPS DI SMAN 14 PEKANBARU TAHUN AJARAN 2015/2016 - Fadillah, Abdi; Umari, Tri; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the effect Effect Against Self-ControlInformation Service Class X SMAN 14 Pekanbaru IPS In the academic year 2015/2016. This research was conducted in SMA Negeri 14 Pekanbaru from March 2016 to May2016. The method used is a method of real- experimental with patterns pretest - posttestcontrol group design . Research subjects in this study were students of class X SMA 14Pekanbaru with a low level of self-control . Based on the correlation coefficient betweenx1 and x2 is the determinant coefficient of 0.67 and r2 = 0.45 . This means that thecontribution of information services to the restraint of students by 45 % . Paired t test ofcalculation Sample t -test , obtained = 7.532 with sig ( 2 - tailed) 0,000 Due to the valueof <0.05 ( p < 0.05 ) can be deduced